Приемные устройства мм-диапазона для систем связи и вещания - Sunduchkov, I. K. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The results of the development of receiving devices in the millimeter wavelength range intended for communication and broadcasting systems are presented. The development results of low-noise amplifiers up to 50 GHz and a signal level limiter in a low-noise amplifier at 36 GHz are demonstrated.